Posisi dan Kontribusi Hukum Adat Ketatanegaraan dalam Hukum Tata Negara Indonesia - Surya Mukti Pratama (CV Rewang Rencang, 2021)
The legal policy of recognition of indigenous peoples as outlined by the 1945 Constitution requires the government to make customary law a source and inspiration in the development of national law. In the field of private law such as land and inheritance law, customary law has been elaborated a lot into national law. However, constitutional customary law is still not elaborated so that it often seems that it does not make a good contribution to the development of constitutional law in Indonesia. Based on research it is known that constitutional customary law is a formal source of constitutional law that hierarchically falls under the constitutional law act. In fact, some constitutional customary laws have been adopted in positive constitutional law, such as the provisions regarding the indigenous legal alliance, and the concept of the president as the holder of power over the army.